Posner-Schlossman Syndrome in Common Variable Immunodeficiency - Madiha Huq; Neha Sanan; Phuong Daniels; Robert Hostoffer (Case Reports in Ophthalmological Medicine)
Introduction. Posner-Schlossman syndrome (PSS) is a rare glaucomatocyclitic crisis with clinical features including recurrent episodes of unilateral elevated intraocular pressure. Autoimmune and infectious causes have been proposed as potential etiologies of PSS. We report the first case of PSS in the setting of common variable immunodeficiency (CVID). Case Report. A sixty-two-year-old Caucasian female with a medical history of CVID and ulcerative colitis presented to the emergency room with complaints of acute right-sided vision changes. She reported image distortion, blurriness, and loss of central vision. Physical exam was significant for mildly injected right conjunctiva, visual acuity of 20/70 in right eye, and 20/25 in left eye. The right intraocular pressure was measured at 34 mmHg and left at 12 mmHg. The gonioscopy and dilated fundus examination were unremarkable. Cup to disc ratio was within normal limits, and no afferent pupillary defects were recorded. The patient was acutely treated with three rounds of dorzolamide/timolol and 0.2% brimonidine which decreased the right eye intraocular pressure to 24 mmHg. On follow-up exam with an ophthalmologist, anterior uveitis including an elevated pressure of 41 mmHg on the right and 18 mmHg on the left eye was noted and a PSS diagnosis was confirmed. Conclusion. PSS remains a rare condition with uncertain etiology and no associated systemic conditions. PSS has been postulated to be linked to autoimmune conditions. CVID is associated with many autoimmune disorders including Sjogren’s, rheumatoid arthritis, and colitis. There have been a few reported CVID-associated ocular diseases including granulomatous uveitis and conjunctivitis, chronic anterior uveitis, and birdshot retinopathy. We describe the first case of PSS in a patient with CVID.